The relationship between political legitimacy and economic legitimacy: empirical explorations of a novel research approach on legitimacy - Ignácz, Zsófia S. (Frontiers in Political Science, 2024)
The paper outlines key points of a novel research approach to empirically investigate the question of legitimacy in modern societies. This new research approach utilizes a functionalist perspective to expand the concept of legitimacy. Accordingly, the conceptual framework discusses how legitimacy can be employed in different domains of society. In particular, it proposes to conceptualize both the legitimacy of the political system (political legitimacy) as well as the legitimacy of the economic system (economic legitimacy). The main objectives of the study are to (1) develop conceptualizations that are empirically plausible for the two types of legitimacies; (2) to empirically verify the operationalization; and (3) to assess empirically the relationship between these two types of legitimacies and identify interdependencies between them. The paper employs a macro-level research design to understand the relationship between political and economic legitimacy, where the main units of analysis are countries. The study compiles a new country-level dataset of indicators for political and economic legitimacy based on a large selection of secondary cross-national data sources. It employs then structural equation modeling to established empirical measurement models for political and economic legitimacy. Moreover, the relationship of political and economic legitimacy is explored with a cross-lagged panel model. The paper establishes that political and economic legitimacy are two distinct concepts empirically. Furthermore, the empirical results indicate that political legitimacy has a negative influence on economic legitimacy, whereas economic legitimacy does not effect political legitimacy. Overall, the paper shows the viability of this new research approach and potential pitfalls for future research. The empirical evidence should be interpreted with caution due to low data quality, nonetheless the paper contributes to taking a step closer toward understanding how governments can ensure stable societies.